Occupational and residential segregation - Flückiger, Yves, 1955-; Reardon, Sean F.; Silber, Jacques (Research on economic inequality, 2009)
Although the measurement of segregation by gender or ethnic group in the labor force has long been of interest to both sociologists and economists, the sociology and economics literatures on this topic have evolved in different ways and remained largely separate. This has also been the case to some extent with research on the measurement of residential segregation. Although much of the segregation measurement literature is in sociology and geography, economists have contributed to this field as well, particularly in the development of measures of residential income segregation. Again, however, the economics literature has remained largely separate from that in geography and sociology. Because of this separation, Yves Flückiger and Jacques Silber took the initiative to organize on July 1-6, 2007, an international conference that took place in Monte Verità, in Ascona, Switzerland, devoted to the topic "New Frontiers in the Field of Segregation Measurement and Analysis." The idea was to bring together specialists from several fields of social sciences, all of them working on subjects related to segregation measurement. The present volume gathers some of the papers that were presented at this conference as well as a few papers by authors who did not participate in this event. All the chapters in this volume have been reviewed by referees.